2016
DOI: 10.1002/jmri.25237
|View full text |Cite
|
Sign up to set email alerts
|

Variability and bias assessment in breast ADC measurement across multiple systems

Abstract: Purpose To assess the ability of a recent, anatomically-designed breast phantom incorporating T1 and diffusion elements to serve as a quality control device for quantitative comparison of apparent diffusion coefficient (ADC) measurements calculated from diffusion-weighted MRI (DWI) within and across MRI systems. Materials and Methods A bilateral breast phantom incorporating multiple T1 and diffusion tissue mimics and a geometric distortion array was imaged with DWI on 1.5 T and 3.0 T scanners from two differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 26 publications
3
36
0
Order By: Relevance
“…Third, this was a multicenter clinical trial, so MRI scanners with different magnet strengths (1.5T, 3T) from different vendors were used to acquire data. The phantom study by Keenan et al reported that ADC values vary among vendors and magnet strengths . Newitt et al recently investigated multisite concordance of ADC measurements across the National Cancer Institute's quantitative imaging network and found discrepancies between different platforms .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, this was a multicenter clinical trial, so MRI scanners with different magnet strengths (1.5T, 3T) from different vendors were used to acquire data. The phantom study by Keenan et al reported that ADC values vary among vendors and magnet strengths . Newitt et al recently investigated multisite concordance of ADC measurements across the National Cancer Institute's quantitative imaging network and found discrepancies between different platforms .…”
Section: Discussionmentioning
confidence: 99%
“…The phantom study by Keenan et al reported that ADC values vary among vendors and magnet strengths. 32 Newitt et al recently investigated multisite concordance of ADC measurements across the National Cancer Institute's quantitative imaging network and found discrepancies between different platforms. 24 Fourth, the patient cohort of this study was taken from the experimental arms of four different completed drugs in I-SPY 2.…”
Section: Discussionmentioning
confidence: 99%
“…An initial study with the phantom revealed geometric distortions in the right‐left orientation of the axial plane with echo planar diffusion‐weighted images (Fig. ) across systems (fields and platforms) dependent on which side of the coil the object was located . The distortions remained in the right/left orientation regardless of the phase‐encoding direction, did not change with b ‐value, and thus are most likely due to B 0 inhomogeneity .…”
Section: Deployed Nist Reference Objectsmentioning
confidence: 98%
“…NIST created three reference objects that have been commercialized and are being actively used by the MRI community: the ISMRM/NIST system phantom, 7,21 the QIBA/NIH/ NIST isotropic diffusion phantom, 3,22,23 and the University of California San Francisco (UCSF)/NIST breast phantom. 4,5 The NIST reference objects have been used to identify measurement errors and then improve the stability of acquisitions in technique/pulse sequence development and protocol development for multisite studies. These reference objects were necessary to aid standardization, but they are insufficient given the wide range of qMRI applications-that is, there is still a need for additional reference objects.…”
Section: Deployed Nist Reference Objectsmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) has been adopted as an important tool for the screening and diagnosis of breast cancer . Diffusion‐weighted imaging (DWI), a common functional MRI technology, is widely used to describe the diffusion of water in living tissue by the apparent diffusion coefficient (ADC) . The ADC quantifies the monoexponential decay of signal intensity (SI), which reflects information related to the tumor microenvironment, such as cellularity, extracellular space, and the integrity of the cell membranes in a noninvasive manner .…”
mentioning
confidence: 99%